2015
DOI: 10.1377/hlthaff.2015.0422
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Staffing Hours At Nursing Homes With High Concentrations Of Minority Residents, 2001–11

Abstract: Recent increases in state Medicaid payments to nursing homes have the potential to reduce disparities in nurse staffing between facilities with high and low concentrations of racial/ethnic minority residents. Analyses of nursing home and state policy survey data for the period 2001–11 suggest that registered nurse and licensed practical nurse staffing levels increased slightly during this period, regardless of racial/ethnic minority resident concentration. Adjusted disparities in registered nurse hours per res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…As a result, many nursing homes lack the necessary resources, expertise, and financial incentives to serve residents with behavioral health issues appropriately (Li, 2010; Muramatsu & Goebert, 2011; Reichman et al, 1998). This issue is particularly salient for nursing homes predominated by racial and ethnic minorities, which are oftentimes low-resource and poor-staffed facilities (Fennell et al, 2010; Li, Harrington, Mukamel, et al, 2015; Li, Harrington, Temkin-Greener, et al, 2015; Mor et al, 2004). It is therefore critical that efforts be made to improve both the overall quality of behavioral health care in nursing homes, and the culture sensitivity of such care given the increased diversity of ethnicities and cultural backgrounds of their residents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, many nursing homes lack the necessary resources, expertise, and financial incentives to serve residents with behavioral health issues appropriately (Li, 2010; Muramatsu & Goebert, 2011; Reichman et al, 1998). This issue is particularly salient for nursing homes predominated by racial and ethnic minorities, which are oftentimes low-resource and poor-staffed facilities (Fennell et al, 2010; Li, Harrington, Mukamel, et al, 2015; Li, Harrington, Temkin-Greener, et al, 2015; Mor et al, 2004). It is therefore critical that efforts be made to improve both the overall quality of behavioral health care in nursing homes, and the culture sensitivity of such care given the increased diversity of ethnicities and cultural backgrounds of their residents.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses thus further accounted for common nursing home characteristics that may be associated with staff care practices and performance such as ownership, census of Medicaid-financed residents or racial/ethnic minority residents, and nurse staffing levels (see Table 1 for a full list of nursing home variables). Previous studies have shown that for-profit ownership of the nursing home, for example, tends to predict lower quality of depression care (Gaboda et al, 2011; Siegel et al, 2012) and predominance of a facility by Medicaid or minority residents is associated with lower nurse staffing level, more deficiencies in care, and lower financial resources for staff training or performance improvement (Fennell et al, 2010; Li, Harrington, Mukamel, et al, 2015; Li, Harrington, Temkin-Greener, et al, 2015; Mor et al, 2004).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary analyses suggested nonlinear associations of facility-level racial/ethnic composition with focused outcomes. Thus, similar to previous studies, [14][15][16] we categorized nursing homes into quartiles to capture such nonlinear associations: nursing homes with low proportions of racial/ethnic minority residents (<2.92%, the 25th percentile), medium proportions (2.92%-11.11%, the median), medium-high proportions (11.11%-30.18%), and high proportions (≥30.18%, the 75th percentile). From the NHC files, we obtained a set of nursing home covariates that were found important to COVID-19 infections or deaths, [16][17][18][19] including number of beds, average daily resident census, ownership status (for profit, nonprofit, or government owned), chain affiliation (yes/no), whether the nursing home is affiliated with a hospital, percentage of Medicare residents, percentage of Medicaid residents, average staffing levels (hours per resident day) for RN and for all nursing staff (including RNs, LPNs/LVNs, and certified nursing assistants) in 2019, and five-star ratings for overall quality of care.…”
Section: Variablesmentioning
confidence: 99%
“…47 These disparities have continued over time in nursing homes with high concentrations of minority residents. 48,49 Disparities also occur for nursing home residents paid for by both Medicare (for aged and disabled) and Medicaid (for low-income individuals). These dualeligible residents are more likely to be discharged from hospitals to poorer quality nursing homes with a higher share of Medicaid patients and fewer nurses compared to individuals paid by Medicare only.…”
Section: Other Quality Problemsmentioning
confidence: 99%